The Influence of Family, Church, and School Education on The Character of Christian Children Toward a Golden Indonesia 2045 - Sri Mulyani; Tatag Mulyani; Maya Malau; Sutrisno Sutrisno; Marthin Steven Lumingkewas (South Sulawesi Education Development (SSED), 2024)
Research on the influence of family, church, and school education on the character of Christian children towards a Golden Indonesia 2045, aims to measure how strong the influence of education from the three institutions is. The research was conducted on students at Erenos Junior High School, South Tangerang, with a total of 151 students. The research method was quantitative, using a different test approach, determining the number of samples using the Slovin method. The research results showed that the influence of family education on the character of Christian children was 0.615, church education on the character of Christian children was 0.637, and school education on the character of Christian children was 0.573, all in the strong category. Together, the influence of family, church, and school education on the character of Christian children is 0.630, balanced and equally strong. Christian religious education as a basis for forming strong character will make students have a strong Christ character, to ward off the phenomenon of moral decline. A strong Christian character will equip children to meet the success of Golden Indonesia 2045 and support the success of the Indonesian nation in reaping the Demographic Bonus